ANALYSIS OF ENERGY SERVICE QUALITY USING KANO MODEL TOWARDS INDONESIA'S EMISSION-FREE 2060 - Fanani, Angga Akbar; Wahyudi, Slamet; Kusumaningdyah, Widha; Rahmani, Rizkianuri; Aryanti, Sabrina Putri; Safitri, Eka Rachmadhani; Sapriadi; Wijaya, Salsabila Sulthanah Putri (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
Electricity is a basic necessity in daily life. The 3.55% increase in electricity distribution to Indonesian households has driven people to seek alternative clean energy sources, considering that the majority of energy comes from fossil fuels with high carbon emissions. The government-owned electric power provider has begun to face high levels of complaints, prompting a review of service quality by Law No. 20 of 2002. This study employs a questionnaire method, processed using the Kano model, to analyze the performance of service quality variables provided by a government-owned electric power provider. Based on the Kano analysis, three categories of attributes need to be considered to improve customer satisfaction: One-Dimensional (must be prioritized), Attractive (needs to be maintained), and Indifferent (less attention needed). The one dimensional attributes involve power quality, output stability, service satisfaction, responsiveness during disturbances, service usage costs, and frequency of power disturbances. The better and worse assessments indicate that output stability, electricity costs, and responsiveness during disturbances have a significant impact on increasing customer satisfaction, while their inadequacy in these attributes can lead to a significant decrease in satisfaction.